2015
DOI: 10.1093/infdis/jiv456
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Statins on Influenza Vaccine Response in Elderly Individuals

Abstract: Influenza vaccination strategies have targeted elderly individuals because they are at high risk of disease complications and mortality. Statins are a class of drugs used to treat hypercholesterolemia and are frequently used in the elderly population to reduce the risk of cardiovascular disease. However, statins are also known to have immunomodulatory effects that could impact influenza vaccine response. In a post hoc analysis, we performed a cross-sectional observational study nested within a comparative immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 17 publications
2
61
3
Order By: Relevance
“…A posthoc analysis of data from a randomized clinical trial comparing MF59-adjuvanted IIV3 and unadjuvanted IIV3 among persons aged ≥65 years demonstrated lower geometric mean titers following vaccination among persons receiving chronic statin therapy (by 38% [95% CI = 27-50] for A(H1N1), by 67% [95% CI = 54-80] for A(H3N2), and by 38% [95% CI = 28-49] for B). The effect was more pronounced among those receiving synthetic statin drugs (fluvastatin, atorvastatin, and rosuvastatin) relative to those receiving fermentation-derived statins (pravastatin, simvastatin, lovastatin, and Advicor) (213). A retrospective cohort study covering nine influenza seasons found reduced effectiveness of influenza vaccine against MAARI among statin users (214); however, this study did not evaluate confirmed influenza illness.…”
Section: Persons With Chronic Medical Conditionsmentioning
confidence: 90%
“…A posthoc analysis of data from a randomized clinical trial comparing MF59-adjuvanted IIV3 and unadjuvanted IIV3 among persons aged ≥65 years demonstrated lower geometric mean titers following vaccination among persons receiving chronic statin therapy (by 38% [95% CI = 27-50] for A(H1N1), by 67% [95% CI = 54-80] for A(H3N2), and by 38% [95% CI = 28-49] for B). The effect was more pronounced among those receiving synthetic statin drugs (fluvastatin, atorvastatin, and rosuvastatin) relative to those receiving fermentation-derived statins (pravastatin, simvastatin, lovastatin, and Advicor) (213). A retrospective cohort study covering nine influenza seasons found reduced effectiveness of influenza vaccine against MAARI among statin users (214); however, this study did not evaluate confirmed influenza illness.…”
Section: Persons With Chronic Medical Conditionsmentioning
confidence: 90%
“…These effects were observed in both the adjuvanted and nonadjuvanted vaccine groups in the clinical trial. These results, if confirmed, could have implications both for future clinical trial designs, as well as vaccine use recommendations for the elderly (12). Also in another study, statin therapy was associated with reduced influenza VE against medically attended acute respiratory illness (MAARI).…”
mentioning
confidence: 76%
“…The findings have potential implications for guidelines regarding statin use in older adults around the vaccination time, but additional studies, including researches examining laboratory-confirmed cases of flu, are needed to provide more guidance (12,13).…”
mentioning
confidence: 97%
“…Moreover, statins may influence the vaccine response (28). In a recent observational study the antibody response to influenza vaccine was found to be significantly lower in elderly (>65 years) statin users compared with non-statin users (29). Blood samples are taken on two occasions; before vaccination and 4 weeks (+/-2-3 days) after vaccination.…”
Section: Accepted Manuscriptmentioning
confidence: 99%